Phenolic composition of hazelnut leaves: Influence of cultivar, geographical origin and ripening stage - Amaral, Joana S. (2011)
Nowadays, hazelnut tree leaf, a byproduct of hazelnut harvesting, is seen as a potential source of natural antioxidants. In this study, the phenolic composition of 93 samples (19 cultivars collected along 3 crop years in 2 geographical locations) was determined to evaluate the influence of genetic and edaphoclimatic factors. Besides, a seasonal pattern variation study was performed, comprising the screening (from May to September) of the phenolic composition of four cultivars under the same agricultural, geographical and climatic conditions. Hazelnut leaf showed to be a good source of total phenolics since its content ranged from 2.5 to 30.5 g/kg. A seasonal pattern was observed consisting of an increase of the total phenolic content from May to July, a considerable decrease in August and a new increase in September. In all cultivars, the highest content of phenolics was achieved in July. Multivariated statistical analysis suggests that phenolics content in hazelnut leaves is mainly affected by the factor “crop year”, although genetic factors can also exert a moderate influence.